VWA3A-derived ependyma promoter drives increased therapeutic protein secretion into the CSF - Ellie M. Carrell; Yong Hong Chen; Paul T. Ranum; Stephanie L. Coffin; Larry N. Singh; Luis Tecedor; Megan S. Keiser; Eloise Hudry; Bradley T. Hyman; Beverly L. Davidson (Elsevier, 2023)
Recombinant adeno-associated viral vectors (rAAVs) are a promising strategy to treat neurodegenerative diseases because of their ability to infect non-dividing cells and confer long-term transgene expression. Despite an ever-growing library of capsid variants, widespread delivery of AAVs in the adult central nervous system remains a challenge. We have previously demonstrated successful distribution of secreted proteins by infection of the ependyma, a layer of post-mitotic epithelial cells lining the ventricles of the brain and central column of the spinal cord, and subsequent protein delivery via the cerebrospinal fluid (CSF). Here we define a functional ependyma promoter to enhance expression from this cell type. Using RNA sequencing on human autopsy samples, we identified disease- and age-independent ependyma gene signatures. Associated promoters were cloned and screened as libraries in mouse and rhesus macaque to reveal cross-species function of a human DNA-derived von Willebrand factor domain containing 3A (VWA3A) promoter. When tested in mice, our VWA3A promoter drove strong, ependyma-localized expression of eGFP and increased secreted ApoE protein levels in the CSF by 2-12× over the ubiquitous iCAG promoter.